The association between early menarche and higher-risk cardiometabolic profile: a dose–response analysis of the Tabari cohort at enrollment phase - Kheradmand, Motahareh; Hamzehgardeshi, Zeinab; Shahhosseini, Zohreh; Mirjalili, Razie; Moosazadeh, Mahmood (Frontiers in Cardiovascular Medicine, 2023)
The association between menarche and greater risk of cardio-metabolic factors is controversial and requires more shreds of evidence. evidences, Therefore, in this study, we aimed to investigate the effect of early menarche on the cardio-metabolic profile in a largescale cohort population.Study Design: Data collected for the enrollment phase of the Tabari Cohort study was utilized for the present study. We analyzed data from 6103 women aged fomfrom 35 to 70 years old. Logistic regression and dose-response (trend analysis) were used utilized to investigate the association between the effect of early menarche on with diabetes, dyslipidemia, obesity, waist circumference (WC), waist-hip ratio (WHR), and waist-to-height ratio (WHtR).Results: Results of adjusted logistic regression analysis showed that the odds of obesity 1.64 (95% CI: 1.36, 1.99, p for trend <0.001), high WC 1.34(95% CI: 1.07, 1.67, p for trend=0.035), high WHR 1.32(95% CI: 1.05, 1.66, p for trend=0.057) and high WHtR 1.83 (95% CI: 1.22, 2.74, p for trend=0.006) was significantly higher in women with early menarche than those with menarche age at ≥ 14. The prevalence of dyslipidemia in women with early menarche was higher than that among women with menarche age at ≥ 14 (79.9% VS 76.6%). However,Although the difference was not statistically significant (P =0.098). Also, each year lower menarche age was significantly associated with a higher chance of diabetes (5%), obesity (10%), WC (5%), and WHtR (13%).The findings of the present study showed the early menarche as a strong predictor for developing obesity and diabetes, raisesraised WC, WHR, and WHtR. Among all factors, menarche age had the highest predictive power for WHtR. As an age-dependent